(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper is on empirical research on vocabulary learning by using an online game as its platform. A qualitative case study was conducted to investigate Year 5 students’ experience of integrating WOW online games in vocabulary learning. The study also aimed to view the difference in learning experience gained by students of diverse race, socioeconomic status, and familiarity with mobile devices. The data was collected via classroom observations, document analysis and a semi-structured focus group interview. 20 Year 5 students were selected from a suburban school in a district in Malaysia. The findings revealed that the students had positive experience in integrating online games (it is called WOW), which were discussed in 4 themes; able to experience fun learning, personalised learning, attractive features, and enjoyable positive reinforcement. A clear difference of experience of integrating online games in vocabulary learning is evident among students from different races, socioeconomic status and levels of familiarity with mobile devices. The findings indicated that a majority of Malay and Indian participants, as well as those from Top and Middle socioeconomic class and have high or moderate level of mobile device familiarity, enjoyed utilising WOW due to the ease of accessing WOW in portable devices and in their own time. However, a number of underprivileged groups, such as students of low socioeconomic status, the Orang Asal (Indigenous) and students with low level of mobile device familiarity, had an unsatisfying experience and faced multiple challenges throughout integrating WOW online game in vocabulary learning. The outcome of this study could provide pertinent knowledge on ESL students’ experience in integrating online educational games. Based on the findings, it is recommended for primary school teachers to integrate online games in expanding students’ vocabulary repertoire through fun learning.